Photon Counting-Based Metrics for Soft Tissue Differentiation in Coronary Plaque Analysis - Denzinger, S; Goldmann, Florian; Wels, Michael; Schöbinger, Max; Neumann, Dominik; Allmendinger, Thomas; Jürgens, Markus; Goldmann, Manuela; Sühling, Michael; Maier, Andreas (2024 IEEE Nuclear Science Symposium (NSS), Medical Imaging Conference (MIC) and Room Temperature Semiconductor Detector Conference (RTSD), 2024)
Photon counting CT is a promising novel improvement for coronary artery disease diagnostics, bypassing limitations of traditional CT angiography such as calcium blooming. We introduce two new methods integrated into our clinical software: The dual energy ratio and the effective Z map. Both aim to enhance tissue differentiation and plaque segmentation, especially for soft and adipose tissue. The dual energy ratio is easy to compute, but requires careful noise reduction and calibration. The effective Z map offers a more robust alternative, potentially reducing susceptibility to noise, but is still vulnerable to overlapping tissue types. While these methods could potentially revolutionize coronary artery disease assessment, successful clinical implementation and evaluation relies on high quality image denoising and available ground-truth data. Overcoming these challenges yields significant improvements in clinical outcomes by aiding in early detection and treatment of vulnerable plaque
Keywords: Measurement; Microwave integrated circuits; Semiconductor detectors; Computed tomography; Noise reduction; Noise; Software